Junior High School Students' Knowledge of the Local Wisdom of Rawa Pening Lake in Relation to Science Learning Materials - Cahyani, Tabita Puspa; Hastuti, Susanti Pudji; Keliat, Natalia Rosa (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: Local wisdom is ideas in an area that are wise, valuable, and become a tradition and are followed by the people there. By integrating local wisdom in the learning process, it will provide more meaning and real experience to students that the surrounding environment contains local wisdom that must be preserved. This research aims to determine the level of knowledge of junior high school students around Rawa Pening lake regarding the local wisdom of Rawa Pening lake in relation to science learning materials. Method: The type of research used is quantitative descriptive research. The subjects of this research were class VIII junior high school students around Rawa Pening lake. The data collection techniques used are observation, interviews, tests and documentation. The instruments used were interview sheets and test questions. The data analysis used is by analyzing student test scores. The local wisdom found around Rawa Pening lake is the tradition and the use of natural resources. Result: Based on the results of the analysis of students' knowledge about the local wisdom of Rawa Pening lake, it was found that 83% (231 student) were in the